2007
DOI: 10.1007/978-3-540-73283-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Web Accessibility Evaluation - A European Perspective

Abstract: The 2002 eEurope Action Plan advocated adoption of the WAI Content Guidelines in public EU web sites. Many of the European countries have performed web accessibility evaluations. Most of the evaluations are based on the Web Content Accessibility Guidelines from W3C/WAI. Still, a range of different evaluation methodologies and scoring schemes are deployed across the member states. This makes it hard to compare the web accessibility status between the different EU countries. The European Accessibility Internet O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…To investigate the current status in the EU, a number of studies have been undertaken [5][6][7][8], targeted mainly to ''public web sites'' (i.e., government, health and online libraries). In order to follow the evolution of web accessibility in Greece, the Human Computer Interaction Laboratory of the Institute of Computer Science of FORTH (ICS-FORTH), in its capacity as the Greek National Contact Centre of the European Design for All e-Accessibility Network (EDeAN), conducts periodical audits regarding the current status of e-Accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the current status in the EU, a number of studies have been undertaken [5][6][7][8], targeted mainly to ''public web sites'' (i.e., government, health and online libraries). In order to follow the evolution of web accessibility in Greece, the Human Computer Interaction Laboratory of the Institute of Computer Science of FORTH (ICS-FORTH), in its capacity as the Greek National Contact Centre of the European Design for All e-Accessibility Network (EDeAN), conducts periodical audits regarding the current status of e-Accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many cases, this is a technical issue beyond the traditional webmaster's knowledge. Whereas accessibility issues are mentioned as being important quality aspects among all four type of web sites as well as in the research literature (Lazar et al, 2004;Snaprud and Sawicka, 2007), we found that the webmaster's knowledge is important, especially in government web sites, where public information and services must be accessible among various user groups with different requirements and needs. The four different views of system quality presented here indicate that system quality may be something very different, depending on the type of web site, as seen from a webmaster's perspective.…”
Section: Tg 73mentioning
confidence: 93%
“…Further, usability requirements are frequently addressed as a means to stimulate efficiency and effectiveness (Bai et al , 2008; Choudrie et al , 2004, 2009; Baker, 2009). Within a government setting, accessibility requirements are also found to be important (Snaprud and Sawicka, 2007) in order to ensure that everyone has the same access to participate in the digital society; additionally, the quality of web site content (Barnes and Vidgen, 2005; Éthier et al , 2006) and trust (Tan et al , 2008) are also relevant. Even though there is a difference between portals, government web sites, private web sites and e‐commerce sites, there are also overlaps that designers and developers need to be aware of in order to focus on the quality aspects that may influence the user's interaction with a web site.…”
Section: Guiding Framework For Grounding the Knowledge Of The Webmaster's Perception Of Web Site Qualitymentioning
confidence: 99%
“…Despite these issues, one might think, from the perspective of authors such as Li, Yen, Lu, and Lin (2012a); Pereira, Ferreira, and Archambault (2015), one of the main causes for the existence of Web accessibility and usability issues is the complexity associated with the existing standards and guidelines that increase the difficulty associated with developing websites that meet the referred regulations. As a result, the majority of the websites' accessibility and usability issues are still to be resolved and as we witness the development and adoption of new and more advanced ICT the more critical it becomes for websites to deliver to their users a universal access warranty (hence ensuring all users, including those with some sort of disability or incapacity, an easy access to the available content) (Snaprud & Sawicka, 2007;Zhang et al, 2015).…”
Section: Healthcare Websites Evaluationmentioning
confidence: 99%